Desain Sistem Kontrol Penggerak Pintu Pagar Otomatis Di Politeknik Jambi - Anielyn Beatris Malango; Sigit Kurniawan; Maizal Isnen; Mahmud Idris (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2021)
The gate in general as access into and out of the yard or house. Generally, the gate is opened manually by sliding it, for the mechanism of opening and closing the gate is mostly opened manually and requires human labor. So the design of the automatic turnstile drive control system was designed to facilitate users in opening and closing without bothering to push or shift the gate that consumes a lot of time and energy. Components used are in the form of an ½ hp 1 phase ac motor, gearbox and ohm switch. For how to operate it using the ohm switch as a controller by raising or lowering the switch ohm lever then the dynamo and gearbox as movers will open and close the gate. From the test results, to open or close the gate with a track length of 3.6 m takes 10 seconds. For further